High heat capacity materials for improving safety of high energy density batteries
Patent Information
- Application Number
- CN202580026108.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-12-20
- Filing Date
- 2025-04-07
- Publication Date
- 2026-11-03
AI Technical Summary
高能量密度锂离子电池在热失控和热传播方面存在安全隐患,尤其是基于硅的电池单元由于低热容量导致温度升高迅速,增加了热失控的风险和扩散可能性。
Introducing materials with high specific heat capacity into the components of the battery cell, such as Al2O3, LiF, Li2O, LiOH, LiOH·H2O, Li2CO3, Mg(OH)2, Al(OH)3, LiAlO2, LiAlF4, BeO, BeF2, Be(OH)2, graphite, amorphous hard carbon, soft carbon, expanded graphite, graphene, carbon nanotubes, carbon fibers, etc., can enhance heat absorption capacity and reduce the rate and extent of temperature rise.
By improving the heat absorption capacity of battery cells, the possibility of thermal runaway is reduced, the rate of temperature rise is slowed down, battery safety is enhanced, the spread of heat propagation is prevented, and the overall safety of the battery is improved.
Smart Images

Figure CN123036704A_ABST
Abstract
Description
[0001] Cross-reference to related applications
[0002] This application claims the benefit and priority of U.S. Provisional Patent Application No. 63 / 575,115, filed April 5, 2024, entitled “CELLS WITH INSULATION PAPERWRAPPING FOR DELAYED HEAT PROPAGATION”. This application also claims the benefit and priority of U.S. Provisional Patent Application No. 63 / 575,185, filed April 5, 2024, entitled “HIGH HEAT CAPACITY MATERIALSFOR IMPROVED SAFETY OF HIGH ENERGY DENSITY BATTERIES”. This application also claims the benefit and priority of U.S. Provisional Patent Application No. 63 / 575,200, filed April 5, 2024, entitled “SAFETY-ENHANCEMENT STATE-OF-CHARGE (SOC) REDUCTION DEVICES FOR PROPAGATION RESISTANTLITHIUM-ION BATTERIES”. Each of these disclosures is incorporated herein by reference in its entirety. Background Technology
[0003] The limitations and drawbacks of conventional materials will become apparent to those skilled in the art by comparing these methods with certain aspects of the methods and systems of this application as illustrated in the remainder of this disclosure with reference to the accompanying drawings. Summary of the Invention
[0004] High heat capacity materials for improving the safety of high energy density batteries, substantially as shown in at least one figure and / or described in conjunction with at least one figure, are set forth more fully in the claims. Attached Figure Description
[0005] Figure 1 The specific heat capacity of graphite and silicon as a function of temperature is shown according to various exemplary embodiments of the present disclosure.
[0006] Figure 2A , Figure 2B and Figure 2C The cumulative heat absorbed by battery cells with different anode compositions according to various exemplary embodiments of the present disclosure is shown.
[0007] Figures 3 to 6 An exemplary battery with anode variation according to various exemplary embodiments of the present disclosure is shown.
[0008] Figure 7 An exemplary heat propagation testing apparatus according to various exemplary embodiments of the present disclosure is shown.
[0009] Figure 8A and Figure 8B Exemplary residues of a battery cell after a thermal propagation test according to various exemplary embodiments of the present disclosure are shown.
[0010] Figure 9 An exemplary battery management system (BMS) for managing battery operation is illustrated according to various exemplary embodiments of the present disclosure.
[0011] Figure 10 This is a flowchart of an exemplary lamination process for forming a silicon-dominant anode cell according to various exemplary embodiments of the present disclosure.
[0012] Figure 11 This is a flowchart of a direct coating process for forming silicon-dominant anode cell cells according to an exemplary embodiment of the present disclosure. Detailed Implementation
[0013] Although the technology described in this article is often described as being combined with silicon cells, it is also applicable to conventional non-silicon cells and their manufacturing processes.
[0014] Heat transfer
[0015] Lithium-ion (LIB) battery cells are commonly used in power tools, electric bicycles, and electric vehicles. However, these batteries can sometimes fail, with thermal runaway (TR) being one possible failure mode. TR is a chain reaction caused by a rapid rise in battery cell temperature due to gas release and uncontrolled flames, leading to cell rupture, decomposition, and explosion. These failures can be caused by mechanical impact, foreign material infiltration, or defects in the electrical, thermal, or manufacturing processes. LIB battery cells have limited tolerance for deviations from their specified temperature and voltage / current ranges. Exceeding these parameters can lead to overcharging and increase the risk of TR. Additionally, if a battery cell is damaged by debris during an accident, it may also enter a TR state.
[0016] Thermal transfer (TP) within a single battery cell can rapidly spread to adjacent cells, especially in large packs used in electric vehicles or energy storage systems. For example, TP within a vehicle's battery pack can endanger the entire vehicle and its occupants. Safety concerns are more pronounced in battery cells with higher energy densities, such as those containing silicon or lithium metal. These cells heat up more rapidly due to their lower thermal capacity compared to traditional graphite or nickel-based cells. High-nickel cathodes such as NMC622, NMC811, NCMA, and NCA can accelerate TP by releasing oxygen, thus exacerbating the problem.
[0017] TP (transfer-induced damage) can lead to significant property damage, injury, and even loss of life. This disclosure provides enhanced safety by reducing or preventing the risks of TP at the pack level and TR (transfer-induced damage) at the cell level.
[0018] High heat capacity materials
[0019] This disclosure improves the safety characteristics of electrochemical devices by incorporating materials with high specific heat capacity, materials undergoing endothermic phase changes or reactions, or combinations thereof, into various components of a battery cell. These materials absorb a large amount of heat during normal operation and, more importantly, reduce the rate and extent of temperature rise during thermal events.
[0020] Specific heat capacity is the amount of heat required to raise the temperature by 1 degree Celsius per unit mass. Specific heat capacity can be measured in joules per kilogram per Kelvin (J / (kg·K)) or joules per gram per Kelvin (J / (g·K)). A temperature change of 1 degree Celsius equals a temperature change of 1 Kelvin. The specific heat capacity of joules per kilogram per Kelvin (J / (kg·K)) is 1000 times that of joules per gram per Kelvin (J / (g·K)).
[0021] Silicon-based lithium-ion battery cells have a lower heat capacity than traditional graphite-based lithium-ion battery cells. Lower heat capacity means less heat is required to raise the temperature of a silicon-based lithium-ion battery cell to its trigger temperature (TR), making it easier to initiate the TR. Lower heat capacity also means that silicon-based lithium-ion battery cells can reach higher temperatures more quickly.
[0022] Figure 1 The specific heat capacity of graphite and silicon as a function of temperature is shown according to various exemplary embodiments of the present disclosure.
[0023] like Figure 1As shown, although both materials have similar specific heat capacities at room temperature, graphite's specific heat capacity exhibits a very steep temperature dependence relative to silicon, reaching approximately twice that of silicon around 1000°C. These differences at the material level lead to significant variations in the thermal conductivity (TR) behavior between Graphite and Si solar cells.
[0024] To reduce the trigger temperature of the thermal regenerative reaction (TR), this disclosure includes materials with a specific heat capacity greater than 1 J / g·K, and preferably, materials with a specific heat capacity greater than 1.5, 2.0, and ideally greater than 2.5 J / g·K at room temperature and ambient pressure. While this disclosure describes examples of integrating materials into the anode, these materials can also be integrated into any component of the electrochemical cell, including but not limited to electrodes, separators, electrolytes, and casings. For nickel-based cathodes exhibiting large exothermic responses during TR, incorporating these additives into the cathode may be more beneficial.
[0025] By increasing the overall heat absorption capacity of the battery cell, these materials help mitigate temperature rises during normal and abnormal operation, thereby reducing the likelihood of thermal runaway (TR).
[0026] This disclosure describes designs for improving the safety characteristics of lithium-ion electrochemical devices, sodium-ion electrochemical devices, or other electrochemical devices. These designs, in addition to reducing the rate and temperature rise during TR to decrease / eliminate flammability, improve heat capacity and reduce or delay TR triggering.
[0027] The battery device disclosed herein includes a battery cell and a high heat capacity material incorporated within the battery cell. The total added weight of the high heat capacity material is less than 20% of the weight of the battery cell. Alternatively, the total added weight of the high heat capacity material is less than 15%, 10%, or 5% of the weight of the battery cell. The battery cell may be a lithium-ion battery cell or a sodium-ion battery cell.
[0028] The material is operable to undergo endothermic phase transitions and / or endothermic phase reactions. The endothermic enthalpy of the material can be greater than 500 J / g (or greater than 750 J / g or 1000 J / g). The material has an endothermic capacity of at least 2,000 J / g (optionally at least 3000 J / g, 4000 J / g, 5000 J / g, 6000 J / g, 7000 J / g or 8000 J / g) at temperatures from 25°C to 1000°C.
[0029] For reference below Figure 2A and Figure 2B As described above, Al2O3 can be added to LIB battery cells. See the following reference... Figure 2BAs mentioned above, LiF, Li2O, LiOH, and LiOH·H2O can be added to the LIB battery cell. Furthermore, Li2CO3, Mg(OH)2, Al(OH)3, LiAlO2, LiAlF4, and / or lithium / beryllium compounds (e.g., BeO, BeF2, Be(OH)2) can also be incorporated into the battery cell.
[0030] For reference Figure 2C The battery cell may also incorporate additional graphite or amorphous hard / soft carbon, expandable graphite, expanded graphite, graphene, fullerene, carbon nanotubes (SWCNT / MWCNT), carbon fibers, carbon-carbon composites, or any other carbon allotropes. For example, the anode may include graphite (Gr), silicon (e.g., Si or SiOx), and / or lithium (Li) metal to improve thermal capacity, thereby reducing the rate and temperature rise during TR, as well as the ease of triggering TR.
[0031] The battery device may incorporate non-flammable / flame-retardant electrolyte components with high specific heat capacity and / or high boiling point and / or enthalpy of vaporization, including but not limited to phosphazenes, ionic liquids, phosphite / phosphate-based solvents (such as TMP (trimethyl phosphate), TEP (triethyl phosphate), TFEP (tris(2,2,2-trifluoroethyl) phosphate), high-boiling-point hydrofluoroethers (such as (1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,2,2-tetrafluoroethyl-1H,1H,5H-octafluoropentyl ether, Novec-7300, 7500, etc.), perfluoroethers, perfluorocarbon solvents, hydrofluorocarbon solvents, etc.
[0032] Battery devices can incorporate non-flammable / low-flammable polymers with high specific heat capacity, such as Teflon (PTFE), PVDF, PVC, polyvinylidene chloride, etc.
[0033] Battery devices can incorporate polymers / waxes with high specific heat capacity, such as rubber, paraffin wax, hydrofluoric wax, fluorinated paraffin wax, lignin, furfural, phenolic resin, epoxy resin, cellulose-based polymers, PET, polyamide, polyimide, PVA, PEEK, PEO, PEG, aramid, polycarbonate, polyethylene, polyarylacetylene, polystyrene, PAN, PMMA, polypropylene, silicone, Teflon, PVDF, PVC, polyvinylidene chloride, etc., as well as flame retardant additives such as APP (ammonium polyphosphate), triphenyl phosphate, brominated flame retardants, etc., to reduce / eliminate flammability.
[0034] To further enhance safety, this disclosure also includes materials that undergo endothermic phase transitions or reactions within the battery cell assembly. These materials have an endothermic enthalpy greater than 500 J / g, and alternative embodiments utilize materials with endothermic enthalpies greater than 750 J / g and 1000 J / g. The incorporation of these materials allows the battery cell to absorb more heat during thermal events, providing a critical buffer against thermal shock (TP).
[0035] In another embodiment, materials exhibiting both high specific heat capacity and significant endothermic behavior are selected. These materials can exhibit a sharp increase in specific heat capacity (from 1 J / kg·K² to 4 J / kg·K²) with increasing temperature, or they can undergo endothermic reactions or phase transitions. Therefore, the overall endothermic capacity of the battery cell is significantly enhanced, potentially reaching levels greater than 2000 J / g, and alternative embodiments achieving levels greater than 3000, 4000, 5000, 6000, 7000, or even 8000 J / g in the temperature range of 25°C to 1000°C.
[0036] Figure 2A The cumulative heat absorbed (denoted as Q(J)) by battery cells with graphite, silicon, and silicon-alumina loaded on the anode is shown in Table 1 below:
[0037] Table 1: Design parameters of different NCM811 battery cells for TP testing
[0038] Under adiabatic conditions, all components are the same except for the anode. Figure 2A This indicates that the same amount of heat is required to raise the temperature of a graphite solar cell from room temperature to ~820°C, while the equivalent silicon solar cell reaches temperatures exceeding 1400°C. This is because the heat capacity of the Graphite solar cell at room temperature is about 30% higher than that of the equivalent Si solar cell (due to the lower mass energy density of the Graphite solar cell), but this is amplified by the steeper temperature dependence.
[0039] When 5.8 mg / cm³ is added to the Si anode 2 When aluminum oxide (Al2O3) was used to improve heat capacity, the highest temperature recorded during the TP test dropped to ~1250℃.
[0040] As shown in Table 2 Figure 2B The cumulative heat absorbed by battery cells with different additives loaded on the anode is shown:
[0041] Table 2: Design parameters of different NCM811 battery cells with different anode additives
[0042] The additives provided in Table 2 exhibit higher specific heat capacity than graphite at room temperature and still show a strong temperature dependence. These materials do not interfere with the operation of the battery cell and remain electrochemically inert during normal battery cell operation. These materials also possess high density, which minimizes the volumetric energy density loss caused by their incorporation. Figure 2B As shown, these materials do not volatilize or sublimate below 1000°C, meaning they will remain within the battery within the temperature range experienced by the cell during TR (Transient Thermal) operation. These materials should not react with other materials, nor should they themselves react and release heat in exothermic reactions. These materials are easy to process, cost-effective, and sustainably sourced.
[0043] In addition, LiF and LiOH melt at approximately 460 °C and 850 °C, respectively, with endothermic enthalpies of fusion of approximately 972 J / g and 1044 J / g, which can also contribute to heat absorption during the TR process and help reduce temperature rise.
[0044] LiOH·H2O can be advantageous for battery cells (such as LFP and low-nickel), where the temperature rise is maintained below 800°C. Beryllium-based compounds can be advantageous in situations where no human contact is expected during operation.
[0045] This disclosure also provides compositions of the above-mentioned materials, particularly those with high heat capacity and non-flammable properties, wherein the total added weight of these materials is less than 20% of the total weight of the battery cell. Alternatively, the added weight may be limited to less than 15%, 10%, or 5%.
[0046] Figure 2C The effect of Si content (by weight) on the heat absorption capacity of a cell with a designed Si-Gr anode, which is designed to have the same capacity as the graphite cell defined in Table 1, is shown.
[0047] This disclosure is beneficial for the design of high-energy-density battery cells, such as those with an anode containing more than 5% silicon by weight. In such designs, the risk of thermal runaway (TR) increases due to the high temperatures that can be reached during operation. The proposed materials are incorporated (see reference). Figure 2B The risk has been significantly reduced by enhancing the battery cell’s ability to absorb and dissipate heat.
[0048] like Figure 2CAs shown, a Si-Gr cell design containing only 10% by weight of Si produced a TR temperature exceeding 1000°C. Therefore, the additives disclosed herein are most useful for cell designs with an anode containing >5% Si (optional ranges: >10% Si, >15% Si, >20% Si, 25% Si). This is also applicable to any other high-energy-density cell design (e.g., anode-less lithium metal cell, other high-capacity alloy anodes: Ge, aluminum, boron, etc.).
[0049] Battery Example
[0050] Figure 3 An example battery with anode variation is shown. (Reference) Figure 3 The battery shown includes a separator 103 sandwiched between an anode 101 and a cathode 105, and current collectors 107A and 107B. A load 109 coupled to the battery is also shown, illustrating an example when the battery is in discharge mode. In this disclosure, the term "battery" can be used to refer to a single electrochemical cell, multiple electrochemical cell units forming a module, and / or multiple modules forming a pack. Furthermore, Figure 3 The battery shown is a very simplified example, intended only to illustrate how a lithium-ion battery cell works.
[0051] The development of portable electronic devices and the electrification of transportation have driven the demand for high-performance electrochemical energy storage. In devices ranging from small-scale (<100 Wh) to large-scale (>10 kWh), LIBs are widely used compared to other rechargeable battery chemistry due to their advantages in energy density and cyclability.
[0052] Anode 101 and cathode 105, together with current collectors 107A and 107B, may include electrodes, which may be contained within or comprise plates or films of an electrolyte material, wherein the plates may provide a physical barrier containing the electrolyte and conductive contact with external structures. In other embodiments, the anode / cathode plates are immersed in an electrolyte, while a housing provides an electrolyte container. Anode 101 and cathode 105 are electrically coupled to current collectors 107A and 107B, which include metals or other conductive materials for providing electrical contact to the electrodes and for providing physical support for the active material during electrode formation.
[0053] Figure 3The configuration shown illustrates a battery in discharge mode, while in a charging configuration, the load 109 can be replaced with a charger to reverse the process. For example, in one type of battery, the separator 103 is typically a thin film material made of, for example, an electrically insulating polymer, which prevents electrons from flowing from the anode 101 to the cathode 105 and vice versa, while being sufficiently porous to allow ions to pass through the separator 103. Typically, the separator 103, cathode 105, and anode 101 materials are individually formed as sheets, films, or foils coated with active materials. In this regard, different methods or processes can be used to form the electrodes, particularly the anode, which is predominantly silicon (>50% active material by capacity or weight). For example, lamination or direct coating can be used to form a silicon-containing anode (silicon anode). The sheets of cathode, separator, and anode are then stacked or rolled with the separator 103 separating the cathode 105 and anode 101 to form the battery 100. In some embodiments, the separator 103 is a sheet, and winding methods and stacking are typically used in its manufacture. In these methods, the anode, cathode, and current collector (e.g., electrode) can contain thin films.
[0054] In the example scenario, the battery may include a solid, liquid, or gel electrolyte. The separator 103 is preferably insoluble in a typical battery electrolyte, which may include, for example, compositions such as ethylene carbonate (EC), fluoroethylene carbonate (FEC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), etc., and dissolved LiBF4, LiAsF6, LiPF6, and LiClO4, LiFSI, LiTFSI, etc. In the example scenario, the electrolyte may contain lithium hexafluorophosphate (LiPF6) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), which can be used together in various electrolyte solvents. Lithium hexafluorophosphate (LiPF6) may be present at a concentration of about 0.1 mol (M) to 4.0 mol (M), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) may be present at a concentration of about 0 mol (M) to 4.0 mol (M). The solvent may comprise, in various percentages, one or more cyclic carbonates such as ethylene carbonate (EC), fluoroethylene carbonate (FEC), or propylene carbonate (PC), and linear carbonates such as ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dimethyl carbonate (DMC). In some embodiments, the electrolyte solvent may contain one or more of EC, FEC, and / or EMC by weight, from about 0% to 40% of EC, from about 2% to 40% of FEC, and / or from about 50% to 70% of EMC.
[0055] The separator 103 can be immersed in a liquid or gel electrolyte. Furthermore, in the example embodiment, the separator 103 does not melt at temperatures below about 100°C to 140°C and exhibits sufficient mechanical properties for battery applications. During operation, the battery undergoes expansion and contraction of the anode 101 and / or the cathode 105. In the example embodiment, the separator 103 can expand and contract by at least about 5% to 10% without tearing or otherwise failing, and can also be flexible.
[0056] The membrane 103 may be sufficiently porous to allow ions to pass through once wetted by, for example, a liquid or gel electrolyte. Alternatively (or additionally), the membrane may absorb electrolytes through gelation or other processes, even without significant porosity. The membrane 103 is typically not too porous to prevent electron transfer between the anode 101 and cathode 105.
[0057] Anode 101 and cathode 105 comprise electrodes for the battery, providing electrical connection to the device for transferring charge during charging and discharging. For example, anode 101 may comprise silicon, carbon, or a combination of these materials. Typical anode electrodes comprise carbon materials and current collectors, such as copper sheets. Carbon is commonly used because of its excellent electrochemical properties and electrical conductivity. Anode electrodes currently used in rechargeable lithium-ion battery cells typically have a specific capacity of approximately 200 mAh / g. Graphite is the active material used in most lithium-ion battery anodes, with a theoretical energy density of 372 mAh / g. In contrast, silicon has a high theoretical capacity of 4200 mAh / g. To improve the volumetric and gravimetric energy densities of lithium-ion batteries, silicon can be used as the active material for cathode 105 or anode 101. Silicon anodes may exist in the form of a composite on the current collector, with >50% silicon by capacity or weight in the composite layer.
[0058] In the example scenario, anode 101 and cathode 105 store ions, such as lithium ions, used for charge separation. In this example, as... Figure 3 As shown, in discharge mode, the electrolyte carries positively charged lithium ions from the anode 101 to the cathode 105, and vice versa, through the separator 103 in charge mode. The movement of lithium ions and their reaction with the electrodes in one electrode generates free electrons, which in turn generate a charge on the opposite current collector. Current then flows from the current collector that generated the charge through the load 109 to the other current collector. The separator 103 prevents the flow of electrons inside the battery 100, allows the flow of lithium ions, and prevents direct contact between the electrodes.
[0059] When the battery discharges and provides current, the anode 101 releases lithium ions to the cathode 105 through the separator 103, generating an electron flow from one side to the other through the connected load 109. When the battery is charged, the opposite occurs, with lithium ions released from the cathode 105 and received by the anode 101.
[0060] The materials selected for the anode 101 and cathode 105 are important for reliability and the potential energy density of the battery 100. For example, to compete with internal combustion engine (ICE) technology and allow for the widespread adoption of electric vehicles (EVs), current battery batteries (LIBs) need improvements in energy, power, cost, and safety. High energy and power densities in LIBs have been achieved with the development of high-capacity and high-voltage cathodes, high-capacity anodes, and electrolytes with high voltage stability and interfacial compatibility with the electrodes. Furthermore, the use of low-toxicity materials as battery materials helps reduce process costs and promotes consumer safety.
[0061] While the performance of electrochemical electrodes depends on many factors, it largely depends on the robustness of the electrical contacts between electrode particles and between the current collector and electrode particles. The conductivity of silicon anode electrodes can be improved by adding conductive additives with different morphological properties. Carbon black (Super P), vapor-grown carbon fibers (VGCF), and mixtures of both have been pre-incorporated into the anode to improve conductivity and other properties. The synergistic interaction between the two carbon materials can facilitate electrical contact during the large volume changes of the silicon anode during charging and discharging, and provide the electrode with additional mechanical robustness and mechanical strength (e.g., holding the electrode material in place). These contact points (especially when using high aspect ratio conductive materials) promote electrical contact between the anode material and the current collector to alleviate isolation (island formation) of the electrode material, while also improving conductivity between silicon regions. Graphene and carbon nanotubes can be used because they exhibit similar advantages. Therefore, in some cases, mixtures of two or more of carbon black, vapor-grown carbon fibers, graphene, and carbon nanotubes can be used alone or in combination to obtain benefits in conductivity and other properties.
[0062] Lithium-ion batteries (LIBs) can utilize graphite-dominant anodes, a type of lithium-intercalation anode. However, silicon-dominant anodes offer improvements compared to graphite-dominant lithium-ion batteries. Silicon exhibits higher gravimetric capacity (4200 mAh / g vs. graphite's 372 mAh / g) and volumetric capacity (2194 mAh / cc vs. graphite's 890 mAh / cc). Furthermore, Si has a higher redox potential than graphite, with a voltage plateau of approximately 0.3–0.4 V vs. Li / Li+, which allows it to maintain an open-circuit potential, avoiding undesirable lithium plating and dendrite formation. While silicon exhibits excellent electrochemical activity, achieving stable cycle life with silicon-based anodes is challenging due to the large volume changes during lithiation and delithiation. This is because the large volume changes, coupled with its low conductivity, cause silicon to separate from the surrounding material in the anode, resulting in the silicon region losing electrical contact with the anode.
[0063] Furthermore, large silicon volume changes exacerbate the formation of the solid electrolyte interphase (SEI), which can further lead to electrical isolation and thus capacity loss. During charge-discharge cycling, the expansion and contraction of silicon particles cause them to pulverize, thereby increasing their specific surface area. During cycling, as the silicon surface area changes and increases, the SEI continuously decomposes and reforms. Therefore, during cycling, the SEI continuously accumulates around the pulverized silicon regions, forming a thick electronic and ionic insulating layer. This accumulated SEI increases the electrode impedance and reduces the electrode's electrochemical reactivity, which is detrimental to cycle life. Therefore, silicon anodes require a highly conductive matrix that (a) immobilizes the silicon particles within the anode, (b) is flexible enough to accommodate the large volume expansion and contraction of silicon, and (c) allows for rapid electron conduction within the matrix.
[0064] Therefore, there is a trade-off between the functions of the active material, conductive additives, and polymer binders. This balance can be adversely affected by high-energy-density silicon anodes with low conductivity and the aforementioned large volume change. The polymer binder can be pyrolyzed to produce a pyrolytic carbon matrix with embedded silicon particles. Furthermore, the polymer can be selected from polymers that are completely or partially soluble in water or other environmentally harmless solvents, or mixtures thereof, and compositions thereof. Water-insoluble polymer suspensions can also be utilized.
[0065] In some implementations, dedicated systems and / or software may be used to control and manage the battery or battery pack. In this regard, such dedicated systems may include suitable circuitry for operating and / or performing control and management-related functions or operations. Furthermore, this software may run on suitable circuitry, such as processing circuitry already present in the system (e.g., a general-purpose processing unit), or may be implemented on dedicated hardware. For example, a battery pack (e.g., a battery pack for electric vehicles) may be equipped with a battery management system (BMS) to manage the battery (or pack) and its operation.
[0066] Figure 4 An exemplary SOCD coupled to a coin cell is shown. Reference Figure 2A , Figure 2B and Figure 2C The described additives can be used as follows Figure 4 The side load shown is incorporated into the anode of the battery cell.
[0067] Figure 5 An exemplary SOCD coupled to an electrode stack is shown. (Reference) Figure 2A Figure 2B Figure 2C The described additives can be used as follows Figure 5 The side load shown is incorporated into the anode of the battery cell.
[0068] Figure 6 An exemplary SOCD is shown attached to a cylindrical metal can battery cell. (Reference) Figure 2A Figure 2B Figure 2C The described additives can be used as follows Figure 6 The side load shown is incorporated into the anode of the battery cell.
[0069] TP test
[0070] Figure 7 Exemplary TP testing apparatuses according to various embodiments of the present disclosure are shown.
[0071] like Figure 7 As shown, the TP testing apparatus includes a heater 701 and four pouch-shaped battery cells 703, 705, 707 and 709, located within a heat-resistant ceramic chamber 711 equipped with an infrared window 713.
[0072] During TP testing, heater 701 (e.g., a 200W heater) heats battery cell 1 703, while thermocouples 715, 717, 719, 721, and 723 measure the temperature of heater 701 and the temperature changes between battery cells 703, 705, 707, and 709. Infrared sensors, mounted through infrared window 713, provide accurate temperature and ignition time measurements. The test is conducted in a controlled environment with a ceramic chamber 711 of approximately 1 cubic foot, equipped with a tempered glass viewing window 713. Typically, four battery cells 703, 705, 707, and 709 are stacked together, with the top of one battery cell in contact with the bottom of the next. Only the bottom of the first battery cell 703 is directly on heater 701. No external barriers are placed between the battery cells. Heater 701 covers 20% of the battery cell area, and heating is controlled to achieve a heating rate exceeding 15°C / second. Thermocouple 717 between the heater and the first battery cell 703 measures the heater's heating rate to ensure it meets design specifications. Key test outputs include the time required for TP (heat transfer) and the highest temperature reached by the battery cell.
[0073] Figure 8A An example of Si cell residue after TP is shown.
[0074] Figure 8B An example of Si-alumina cell residue after TP is shown.
[0075] like Figure 8B As shown, the Si-alumina battery cells remained largely intact after TP treatment, while the pure Si battery cells (such as...) Figure 8A Then it completely decomposes. This decomposition shows that the higher the temperature, the more violent the result.
[0076] As mentioned above, the temperature-dependent thermal capacity of the battery cell design affects temperature rise and TR rate. Furthermore, thermal capacity also influences the ease with which TR is triggered. This disclosure provides several strategies to improve the thermal capacity of high-energy-density batteries to reduce the tendency and severity of TR.
[0077] With additional security enhancements
[0078] Additional safety features may be included within the battery cell. All features can be enclosed within a battery cell housing (e.g., a can, bag, or other). This disclosure can be combined with other technologies such as state-of-charge devices, non-flammable electrolytes, electrolytes with high ionic conductivity, high-temperature resistant electrolytes, and insulating layers.
[0079] Within a battery pack, different battery cells can incorporate different technologies, such as alternating high-heat-capacity battery cells. Overall safety design can also depend on pack components, such as heating plates or foam, which may eliminate the need for internal insulation layers or higher heat-capacity designs.
[0080] Safety features designed for high-energy-density devices may include a total energy density exceeding 600 Wh / L. The chemical composition includes silicon. The anode may be silicon-dominant. The chemical composition may include a high-nickel metal oxide containing nickel equal to or greater than that of NCM622. The battery cell may include a high-nickel (cathode) and silicon (anode). The battery cell may include a lithium metal anode.
[0081] Safety devices implemented in battery cells can be manufactured without placing significant interface materials between them (cell-to-pack design). These safety devices can reduce the volumetric or gravimetric energy density of the battery cell by <30%, ideally <20%, <10%, or <5%.
[0082] This disclosure enables high-energy-density chemistry materials such as silicon, lithium metal, and high-nickel cathodes. This disclosure allows for a simpler approach to pack creation by enclosing safety devices within the battery cells. This disclosure allows for cell-to-pack designs with no visible interfaces between battery cells, providing higher pack energy density at a lower cost. This disclosure eliminates the need for complex designs (e.g., those incorporating semiconductor temperature sensors).
[0083] Battery management and manufacturing
[0084] Figure 9 An example battery management system (BMS) for managing battery operations is shown. For example... Figure 9 The image shows the Battery Management System (BMS) 140.
[0085] The battery management system (BMS) 140 may include components configured to manage one or more batteries (e.g., each as shown in the reference). Figure 3 Suitable circuitry (e.g., processor 141) for each of the battery 100 examples. In this regard, the BMS 140 may communicate with and / or be coupled to each battery 100. In some embodiments, a separate processor (e.g., a conventional processor such as an electronic control unit (ECU), microcontroller unit (ECU), etc.), or several such separate processors, may be used and may be configured to handle algorithms or control functions relating to the battery. In these embodiments, these processors may be connected to the battery, for example via processor 141, and thus may be considered part of the BMS 140 and as part of processor 141.
[0086] In some embodiments, battery 100 and BMS 140 can communicate with and / or be connected to each other, for example, via electronic or wireless communication. In some embodiments, BMS 140 can be incorporated into battery 100. Alternatively, in some embodiments, BMS 140 and battery 100 can be combined into a common package 150. Furthermore, in some embodiments, BMS 140 and battery 100 can be separate devices / components and can only communicate with each other when they are in the same system. However, this disclosure is not limited to any particular arrangement.
[0087] Figure 10 This is an example lamination process flow diagram for forming silicon-dominant anode cell cells. The process uses a high-temperature pyrolysis process, layer removal, and lamination process on a substrate to adhere the active material layer to the current collector. This strategy can also be used with other types of anodes, such as graphite, conversion anodes (e.g., transition metal oxides, transition metal phosphides), and other alloy anodes (e.g., Sn, Sb, Al, P, etc.).
[0088] To manufacture the anode, a crude electrode active material is mixed in step 201. During mixing, the active material may be mixed with binders / resins (such as water-soluble PI (polyimide), PAI (polyamide-imide), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium alginate, phenolic resin or other water-soluble resins and mixtures thereof), solvents, rheology modifiers, surfactants, pH modifiers, and conductive additives. For example, the material may include carbon nanotubes / fibers, graphene sheets, metal polymers, metals, semiconductors, and / or metal oxides. For example, silicon powder with a particle size of 1 μm to 30 μm or 5 μm to 30 μm can be dispersed at, for example, 1000 rpm in a polyamide resin, PAI, or PI (15% to 25% solids in N-methylpyrrolidone (NMP) or deionized (DI) water), for example, for 10 minutes. Then, a conjugated carbon / solvent slurry can be added and dispersed at, for example, 2000 rpm, for example, for 10 minutes, to achieve a slurry viscosity of 2000 cP to 4000 cP and a total solids content of about 30% to 40%. The pH of the slurry can be varied from acidic to alkaline, which is beneficial for controlling the solubility, conformation, or adhesion behavior of the water-soluble polyelectrolyte (e.g., polyamide, carboxymethyl cellulose, or polyacrylic acid). Ionic or nonionic surfactants can be added to promote wetting of the slurry or insoluble components used in the coating process substrate. Particle size and mixing time can be varied to configure the electrode coating density and / or roughness.
[0089] Furthermore, the cathode electrode coating layer can be mixed in step 201 and coated (e.g., onto aluminum), wherein the electrode coating layer may comprise a cathode material mixed with the carbon precursor and additives described above for the anode electrode coating layer. The cathode material may comprise lithium nickel cobalt manganese oxide (NMC (also known as NCM):LiNi x Co y Mn z O2, x+y+z=1), lithium iron phosphate (LFP: LiFePO4 / C), lithium nickel manganese spinel (LNMO: e.g., LiNi 0.5 Mn 1.5 O4), lithium nickel cobalt aluminum oxide (NCA: LiNi a Co b Al c O2, a+b+ C =1), lithium manganese oxide (LMO: e.g., LiMn2O4), quaternary systems of lithium nickel cobalt manganese aluminum oxide (NCMA: e.g., Li[Ni 0.89 Co 0.05 Mn 0.05 Al 0.01 O2, lithium cobalt oxide (LCO: e.g., LiCoO2), and other lithium-rich cathode or similar materials, or combinations thereof. Particle size and mixing time can be varied to configure electrode coating density and / or roughness.
[0090] In step 203, the slurry can be coated onto the substrate. In this step, the slurry can be applied at, for example, 2 mg / cm³. 2 Up to 4 mg / cm 2 The load is coated onto a polyester, polyethylene terephthalate (PET), or polyester film, and then dried in step 205 to obtain an anode with a high silicon content and a residual solvent content of less than 15%. This step is followed by an optional calendering process in step 207, in which the film / substrate can be processed into a smooth and dense sheet of material using a series of hard rollers.
[0091] In step 209, the film containing the active material can then be removed from the PET, wherein the active material layer can be peeled off from the polymer substrate. Following peeling, a pyrolysis step 211 can be performed, in which the material is heated to, for example, 600 to 1250°C for 1 to 3 hours, sliced, and vacuum dried using a two-stage process (120°C for 15 hours, 220°C for 5 hours). If a polypropylene (PP) substrate is used, the peeling process can be skipped, and PP may leave approximately 2% carbon residue after pyrolysis.
[0092] In step 213, electrode material can be laminated onto the current collector. For example, a copper foil with a thickness of 5 μm to 20 μm can be laminated at, for example, 0.2 mg / cm³.2 Up to 0.6 mg / cm 2 The nominal load is coated with polyamide-imide (coated in NMP with 6% wt% varnish and dried under vacuum, for example, at 110°C, for example, for 12 to 18 hours). The anode sheet can then be laminated onto a current collector coated with an adhesive. In an example scenario, a heated hydraulic press is used to laminate the silicon-carbon composite film onto the coated copper. Examples of lamination processes include holding the film at 300°C and 3000 to 5000 psi for 30 to 70 seconds to form the finished silicon composite electrode.
[0093] Before the formation process, the battery cell can be evaluated. Measurements may include impedance values, open-circuit voltage, electrode and cell thickness measurements. Formation cycling is defined as any type of charge / discharge within the battery cell, done to prepare for general cycling of the battery cell, and is considered part of the battery cell manufacturing process. Different charge and discharge rates can be used during the formation step. During formation, initial lithiation of the anode may be performed, followed by delithiation. The battery cell may be clamped during formation and / or cycling.
[0094] Figure 11 This is a flow chart of a direct coating process for forming a silicon-dominant anode cell according to an exemplary embodiment of the present disclosure. The process includes physically mixing active materials, conductive additives, and binders together, and directly coating the mixed slurry onto a current collector prior to pyrolysis. This example process includes a direct coating process in which an anode or cathode slurry is directly coated onto copper foil using a binder (such as CMC, SBR, PAA, sodium alginate, PAI, PI, and mixtures and combinations thereof).
[0095] In step 301, the active material can be mixed with, for example, a binder / resin (e.g., CMC / SBR, PI, PAI, or phenolic resin), a solvent (e.g., NMP, water, other environmentally friendly solvents, or mixtures thereof), and a conductive additive. For example, the material may include carbon nanotubes / fibers, graphene sheets, metal polymers, metals, semiconductors, and / or metal oxides. For example, silicon powder with a particle size of 1 μm to 30 μm can be dispersed at, for example, 1000 rpm in a polyamide resin, PAI, PI (15% solids in DI water or N-methylpyrrolidone (NMP)) for, for example, 10 minutes, and then a conjugated carbon / solvent slurry can be added and dispersed at 2000 rpm for, for, for, for, for, 10 minutes, to obtain a slurry with a viscosity of 2000 cP to 4000 cP and a total solids content of about 30% to 40%.
[0096] Furthermore, the cathode active material can be mixed in step 301, wherein the active material may include lithium cobalt oxide (LCO), lithium iron phosphate, lithium nickel cobalt manganese oxide (NMC), lithium nickel cobalt aluminum oxide (NCA), lithium manganese oxide (LMO), lithium nickel manganese spinel, or similar materials or combinations thereof, mixed with the binder used for the anode active material as described above.
[0097] In step 303, the slurry can be coated onto the copper foil. In the direct coating process described herein, the anode slurry is coated onto the current collector with residual solvent, followed by drying and calendering processes to densify it. A pyrolysis step (approximately 500°C to 800°C) is then applied, causing the carbon precursor to be partially or completely converted into glassy carbon or pyrolytic carbon. Similarly, the cathode active material can be coated onto the foil material, such as aluminum. The active material layer can undergo the drying process in step 305 to reduce the residual solvent content. An optional calendering process can be used in step 307, where a series of hard rollers can be used to process the film / substrate into a smoother and denser sheet of material. In step 307, the foil and coating are optionally processed by a rolling mill for calendering, where the surface is smoothed and the thickness is controlled to be thinner and / or more uniform.
[0098] In step 309, the active material can be pyrolyzed by heating to 500°C to 1000°C, causing the carbon precursor to be partially or completely converted into glassy carbon. Pyrolysis can be performed either by rolling or after stamping. If the electrode is pyrolyzed by rolling, it is then stamped into a single sheet after pyrolysis. The pyrolysis step can produce an anode active material with a silicon content greater than or equal to 50% by capacity or weight. In an example scenario, the anode active material layer may contain 20% to 95% silicon. In another example scenario, the anode active material layer may contain 50% to 95% silicon by weight. For example, if the current collecting foil is not pre-stamped / pre-drilled, the formed electrode can be perforated using a stamping roll. The stamped anode can then be used to assemble a battery cell with cathode, separator, and electrolyte materials. In some cases, a separator with significant adhesion properties can be used.
[0099] In step 313, the battery cell can be evaluated prior to the formation process. Measurements may include impedance values, open-circuit voltage, and cell and / or electrode thickness measurements. During formation, initial lithiation of the anode is performed, followed by delithiation. The battery cell can be clamped during formation and / or early cycling. Formation cycling is defined as any type of charge / discharge of the battery cell, done in preparation for general cycling of the battery cell, and is considered part of the battery cell manufacturing process. Different charge and discharge rates can be used in the formation step.
[0100] As used herein, “and / or” means any one or more items in the list connected by “and / or”. As used herein, the term “exemplary” means used as a non-limiting example, instance, or illustration. As used herein, the terms “e.g.” and “for example” set forth a list of one or more non-limiting examples, instances, or illustrations. As used herein, a circuit is “operable” to perform a function, provided it includes the hardware and code necessary to perform that function (if necessary), regardless of whether the function’s performance is disabled or not enabled (e.g., by user-configurable settings, factory adjustments, etc.). As used herein, the term “based on” means “at least partially based on”. For example, “x based on y” means that “x” is at least partially based on “y” (e.g., it may also be based on z).
[0101] Although the methods and / or systems of this disclosure have been described with reference to certain embodiments, those skilled in the art will understand that various modifications and substitutions can be made without departing from the scope of the methods and / or systems of this disclosure. Furthermore, many modifications can be made to adapt specific circumstances or materials to the teachings of this disclosure without departing from its scope. Therefore, the purpose of the methods and / or systems of this disclosure is not limited to the specific embodiments disclosed, but rather to include all embodiments falling within the scope of the appended claims.
Claims
1. A battery device, comprising: Battery cells, and The high heat capacity material is incorporated into the battery cell, wherein the total added weight of the high heat capacity material is less than 20% of the weight of the battery cell.
2. The battery device according to claim 1, wherein the battery cell is one of a lithium-ion battery cell and a sodium-ion battery cell.
3. The battery device according to claim 1, wherein the specific heat capacity varies by at least 0.5 J / (kg) over any temperature range from 25°C to 1500°C. K 2 The material is incorporated into the battery cell.
4. The battery device according to claim 1, wherein the specific heat capacity of the high heat capacity material is greater than 1 J / (g·K) under room temperature and ambient pressure conditions.
5. The battery device according to claim 1, wherein the specific heat capacity of the high heat capacity material is greater than 2.5 J / (g·K) under room temperature and ambient pressure conditions.
6. The battery device of claim 1, wherein a material operable to undergo an endothermic phase change is incorporated into the battery cell.
7. The battery device of claim 1, wherein a material operable to undergo an endothermic phase reaction is incorporated into the battery cell.
8. The battery device according to claim 1, wherein a material with an endothermic enthalpy greater than 500 J / g is incorporated into the battery cell.
9. The battery device according to claim 1, wherein a material with an endothermic enthalpy greater than 1000 J / g is incorporated into the battery cell.
10. The battery device according to claim 1, wherein a material with a heat absorption capacity of at least 2000 J / g is incorporated into the battery cell at a temperature above 25°C.
11. The battery device of claim 1, wherein a material having a heat absorption capacity of at least 2000 J / g at a temperature below 1000°C is incorporated into the battery cell.
12. The battery device according to claim 1, wherein: Beryllium compounds are incorporated into the battery cell, and The beryllium compound is one of BeO, BeF2 and Be(OH)2.
13. The battery device according to claim 1, wherein: Lithium compounds are incorporated into the battery cell, and The lithium compound is one of LiF, Li2O, LiOH, LiO·H2O, Li2CO3, LiAlO2, and LiAlF4.
14. The battery device according to claim 1, wherein: The battery unit is a lithium-ion battery unit. One or more anodes in the battery cell include one or more of the following: graphite, silicon, lithium, Silicon / graphite composites, and Silica / graphite composite, Carbon compounds are incorporated into the battery cell, and The carbon compound includes one or more of the following: graphite, Amorphous hard carbon, Amorphous soft carbon, Expandable graphite Expanded graphite, Graphene, Fullerene, Carbon nanotubes carbon fiber, Carbon-carbon complexes Carbonaceous materials, and Carbon allotropes.
15. The battery device of claim 14, wherein a portion of the carbon compound is inactive.
16. The battery device according to claim 1, wherein: The battery unit is a sodium-ion battery unit, and One or more of graphite and amorphous carbon are incorporated into the battery cell.
17. The battery device according to claim 1, wherein: The battery cell is a sodium-ion battery cell. Inactive compounds are incorporated into the battery cell, and The inactive compound includes one or more of the following: graphite, Amorphous hard carbon, Amorphous soft carbon, graphene, Expanded graphite, Expandable graphite Intercalated graphite, and Carbonaceous materials.
18. The battery device according to claim 1, wherein: The high heat capacity material is a non-combustible compound, and The non-flammable compound includes one or more of the following: Phosphazenes, Ionic liquids Solvents based on phosphites / phosphates Trimethyl phosphate, Triethyl phosphate, Tris(2,2,2-trifluoroethyl) phosphate, High-boiling-point hydrofluoroethers, 1,1,2,2-Tetrafluoroethyl, 2,2,3,3-Tetrafluoropropyl ethyl ether, 1,1,2,2-Tetrafluoroethyl, 1H,1H,5H-octafluoropentyl ether, Novc-7300 Novc-7500 Perfluoroethers Perfluorinated carbon solvent, Hydrofluorocarbon solvents, and Al2O3.
19. The battery device according to claim 1, wherein: The high heat capacity material is a non-combustible polymer, and The non-flammable polymer includes one or more of the following: Teflon (PTFE) PVDF, PVC, and Polyvinylidene chloride.
20. The battery device according to claim 1, wherein: The high heat capacity material is a polymer, and The polymer includes one or more of the following: rubber, paraffin, Hydrofluoric wax, Fluorinated paraffin, Lignin, furfural, Phenolic resin, Epoxy resin, Cellulose-based polymers, PET Polyamide, Polyimide, PVA, PEEK, PEO, PEG, aramid, polycarbonate, Polyethylene, Polyarylacetylene polystyrene PAN, PMMA, Polypropylene, silicone, Teflon PVDF, PVC Polyvinylidene chloride, Ammonium polyphosphate (APP), Triphenyl phosphate, and Brominated flame retardants.
